Issues surrounding the anti-Inflammatory actions of the citrus polymethoxylated flavones - Manthey, John A.; César, Thaïs B. [UNESP] (American Chemical Society (ACS), 2013)
The polymethoxylated flavones in citrus have been evaluated for their in vivo anti-Inflammatory actions in several animal assays. Strong anti-Inflammatory effects were observed following administration of 3,5,6,7,8,3',4'-heptamethoxyflavone (HMF) dissolved in vegetable oil by intraperitoneal (i.p.) injection, but neglibible action was detected following doses of HMF suspended as fine particulates in vegetable oil. This contradiction is shown to be a reflection of differences in the bioavailabilities of HMF following different routes of administration. Evidence of contrasting bioavailabilities among different PMFs is shown through comparisons of the pharmacokinetics of nobiletin and tangeretin administered in rats. ©2013 American Chemical Society.